Pengaruh Social Media Marketing, Harga dan Brand Image Terhadap Minat Beli - Afandi, Dian Rachmawati; Wahyono, Dwi; Widyastuti; Nugraha, Aat Ruchiat; Novita, Yulia (Jurnal EMT KITA, 2024)
The development of modernization is always changing, especially the culinary business has created intense competition to attract buying interest from consumers. This research aims to determine the influence of social media marketing, price and brand image on interest in buying. The sample obtained consisted of 100 respondents. The method used is quantitative by obtaining data from questionnaires via google from. This research uses a multiple linear regression analysis model to analyze the data. The respective research results show that social media marketing has a positive and significant partial influence on interest in buying. Price partially has a significant negative influence on interest in buying. Brand image has a positive and significant partial influence on interest in buying. The results of social media marketing, price and brand image simultaneously have a positive and significant effect on interest in buying. The results of the R Square value are empirically proven to be 67.7% by the variables in this research.